Comparison of Oral and Esophageal Microbiota in Patients with Achalasia Before and After Peroral Endoscopic Myotomy - Takahashi, Kazuya; Sato, Hiroki; Mizusawa, Takeshi; Tominaga, Kentaro; Ikarashi, Satoshi; Hayashi, Kazunao; Mizuno, Ken-ichi; Hashimoto, Satoru; Yokoyama, Junji; Terai, Shuji (Turkish Journal of Gastroenterology, 2021)
Background/Aims: Patients with achalasia have a high incidence of esophageal squamous cell carcinoma (ESCC), which may be associated with alterations in oral and esophageal microbiota caused by food stasis. This study compared the oral and esophageal microbiota of patients with achalasia before and after per-oral endoscopic myotomy (POEM). It also compared patients with achalasia to those with ESCC. Materials and Methods: Six patients with achalasia and 14 with superficial ESCC were prospectively examined. Oral samples obtained from the buccal mucosa using a swab and esophageal samples obtained from the mid-esophagus using a brush via endoscopy were analyzed by 16s rRNA metagenome sequencing. Additionally, endoscopic and histological findings of patients with achalasia before and after POEM were prospectively compared. Results: In patients with achalasia, Streptococcus was most abundant in both the oral and esophageal microbiota, and the oral and esophageal microbiota were significantly different. Although overall structures of the oral and esophageal microbiota did not change after POEM, the relative abundance rate of Haemophilus and Neisseria increased in the esophagus and endoscopic findings of inflammation improved after POEM (p = 0.04). The relative abundance of microbiota was not different among patients with achalasia and those with ESCC. Conclusion: Oral and esophageal microbiota were significantly different in patients with achalasia, and some of the composition of esophageal microbiota changed after POEM. However, these findings and disease-specific microbiota should be further evaluated in large-scale studies.